First Galileo Single-Frequency Occultation Process and Precision Analysis of FengYun3E - Ming Yang; Xiangguang Meng; Haoran Tian; Yueqiang Sun; Qifei Du; Weihua Bai; Bowen Wang; Xianyi Wang; Peng Hu; Guangyuan Tan (Remote Sensing, 2023)
This article proposes a single-frequency occultation method whose core is the reconstruction of a second frequency measurement. We process the actual received Galileo E1 single-frequency occultation observation data of FengYun3E to meet the urgent need for single-frequency Galileo occultation inversion of FengYun3 E/F/G/H satellites. Galileo single-frequency occultation events are globally distributed evenly and have stable quantities. The refractive index products and dry temperature products inverted from the single-frequency occultation data are reliable at altitudes of 5–30 km. The Galileo E1 single-frequency occultation process can effectively improve the output of FengYun3E/GNOS occultation products. These results validate the feasibility and correctness of using FengYun3/GNOS for the actual Galileo single-frequency occultation process. The atmospheric occultation products of Galileo single-frequency occultation increase the quantity of global occultation products and serve as a beneficial supplement to global numerical weather prediction data sources.